Development of Fuzzy Logic Control for Indoor Lighting Using LEDs Group - M. Khairudin; S. Riyanto; Z. Mohammed (Universitas Ahmad Dahlan, 2018)
This paper presents the design and the development of an indoor lighting control based on fuzzy logic controller (FLC). The objective of this study is to demonstrate how the FLC can optimize the lighting based on indoor and outdoor lighting environments. The FLC system uses two inputs with Light Dependent Resistors (LDR) as a sensor at indoor and outdoor lighting environments. The output is Light Emitting Diodes (LEDs) to provide lighting at the room automatically. The Pulse Width Modulation (PWM) is used to adjust the LEDs lighting in the room. FLC has successfully demonstrated performance to control the output of LEDs as needed. If the LDR 1 input as indoor sensor shows dim, it will automatically turn on brightly. The MSE values for simulation and experiment of LDR 1 and LDR 2 were 34.42 and 30.11 respectively. The results of FLC performance in the simulation work are further validated by an experimental work. Experimental results show similarities compared to the simulation results.